‘UZLAH SEBAGAI JALAN MENCARI KEBENARAN DI ERA REVOLUSI INDUSTRI 4.0 - Akbar Imanuddin; Muhammad Iqbal Rahman (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
The massive development of technology in the era of the industrial revolution 4.0 has brought many social changes and, in practice, has changed human life at every level. The number of jobs that are delayed because of smartphones, the inequality of news on social media, and the truth that overflows and is obscured are examples of how life has changed significantly. This indicates that industrial revolution 4.0 does not only bring changes in a positive sense but also in a negative one. Obscurity and vagueness to the truth can, in turn, damage morality and erase human values. ‘Uzlah or separating oneself from humans, is one of the concepts in Sufism recommended by the Prophet Muhammad when slander has become rampant and riots can no longer be extinguished, which today can be seen by the existence of post-truth narratives or denial of truth. Some criticize that committing ‘uzlah is a cowardly act of running away from problems. This criticism cannot be fully justified and cannot be completely refuted – because textually, some have practiced 'uzlah (meditation in mountains, caves, away from crowds). However, 'uzlah has spiritual values ​​that can maintain emotional and mental stability for those who practice it. The paper seeks to contextualize ​​of 'uzlah according to the needs of the times. The results of this paper find that ‘uzlah can be applied today not only to practice spiritual values but also to strengthen one's stance, enjoy life, be happy at work, be measured in action, and promote objective truth. With these values, it is clear that 'uzlah can be used as one a step to find the truth in the post-truth era of the industrial revolution. Perkembangan teknologi yang begitu pesat di era revolusi industri 4.0 telah membawa perubahan sosial yang jauh berbeda dan pada praktiknya telah mengubah kehidupan manusia di setiap lapisannya. Banyaknya pekerjaan yang tertunda sebab telepon pintar, ketimpangan berita di media sosial, kebenaran yang bertimpah dan terkaburkan, merupakan contoh betapa kehidupan telah berubah secara signifikan. Hal tersebut mengindikasikan bahwa revolusi industri 4.0 tidak hanya membawa perubahan dalam arti positif, tapi juga negatif. Ketidakjelasan dan kekaburan terhadap kebenaran pada gilirannya dapat merusak moralitas dan menghapus nilai-nilai kemanusiaan. ‘Uzlah atau memisahkan diri dari manusia merupakan salah satu konsep dalam ilmu tasawuf yang dianjurkan oleh Nabi Muhammad Saw. ketika fitnah telah menjadi-jadi dan huru-hara tidak dapat dipadamkan lagi, yang dewasa ini dapat dilihat dengan adanya narasi post-truth atau ingkar kebenaran. Ada yang mengkritik bahwa beruzlah termasuk tindakan pengecut karena lari dari masalah. Kritik ini tidak bisa dibenarkan sepenuhnya dan tidak bisa dibantah seutuhnya–sebab ‘uzlah secara tekstual (menyendiri di gunung, gua, jauh dari keramaian) ada yang mempraktekkannya. Akan tetapi ‘uzlah memiliki nilai-nilai spriritual yang dapat menjaga kestabilan emosi dan pikiran bagi barang siapa yang mengamalkannya. Tulisan ini berupaya untuk mengkontekstualisasikan ‘uzlah sesuai kebutuhan zaman. Hasil dari tulisan ini menemukan bahwa uzlah dapat diaplikasikan dewasa ini tidak hanya untuk mengamalkan nilai-nilai spiritual, tapi juga dapat memperteguh pendirian, menikmati hidup, bahagia dalam bekerja, terukur dalam bertindak serta mengedepankan kebenaran objektif. Dengan nilai-nilai tersebut, terang bahwa ‘uzlah dapat dijadikan sebagai salah satu langkah mencari kebenaran di era post-truth revolusi industri 4.0.